CÁLCULO DE VALORES DE SPIB (STATISTICAL PASS BY INDEX) PARA CINCO RODOVIAS NO RIO GRANDE DO SUL - ZWIRTES, ANDRÉ D. F.; SPECHT, LUCIANO P.; NOVROTH, RICARDO K.; CALLAI, SERGIO C. (Salão do Conhecimento, 2013)
Resumo